Method for hot press forming steel product and steel product
Through hot-dip coating and specific annealing processes of zinc or zinc alloys, steel with high residual austenite and ferrite microstructure is formed, which solves the problems of steel products' strength, ductility and electrochemical protection during the thermoforming process, and achieves the High strength, ductility and corrosion resistance.
Patent Information
- Application Number
- CN202080091360.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-27
- Filing Date
- 2020-11-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-11-27
AI Technical Summary
The prior art is difficult to achieve high strength, ductility and electrochemical protection of steel products simultaneously during the thermoforming process, and zinc-based coatings are prone to surface cracking and oxidation.
Steel products with hot-dip coated with zinc or zinc alloys are formed through specific continuous annealing and hot-dip galvanizing processes to form steel with high residual austenite and ferrite microstructure, ensuring the adhesion of zinc-based coatings and Mechanical properties of steel.
It achieves high strength, ductility and corrosion resistance, reduces oxidation and microcracks of zinc coatings, and improves the weldability and energy absorption capacity of steel products.
Smart Images

Figure CN114901842B_ABST
Abstract
Description
[0001] The present invention relates to a method for hot press forming a steel product from zinc or zinc alloy coated steel after continuous annealing and subsequently hot press forming the steel product from zinc or zinc alloy coated steel, and to a hot dip zinc or zinc alloy coated steel product manufactured by hot press forming the zinc or zinc alloy coated steel.
[0002] Hot press forming (also known as hot stamping, hot forming, stamping and press hardening) is a technique for forming and hardening a steel blank into a shaped final article or component.
[0003] Typically, the steel billet is reheated to the austenitizing temperature (usually 870-940°C) and soaked at this temperature, followed by forming and press quenching in a die. High temperatures are required to fully austenitize the steel and dissolve all carbides. Press quenching results in a strong martensitic structure in the steel substrate. Even when hot forming is performed in the critical range to form a dual-phase structure, the reheating temperature is 760°C or higher.
[0004] It is known that hot forming of uncoated steel blanks can lead to oxidation. Zn and Al based coatings have been applied to reduce this effect. With regard to corrosion resistance, Zn based coatings may be preferred as they also provide galvanic protection. However, due to the low melting point and high reheating temperature of Zn and Zn-Fe compounds, surface cracking may occur during hot forming, where the cracking is related to the grain boundary penetration of zinc. One approach that has been explored to address this problem is modification of the Zn coating.
[0005] Current (ultra) high-strength hot-formed products have very low service ductility (<8%) due to their martensitic or martensitic-bainitic microstructures obtained by press-quenching. The martensitic microstructure in hot-formed products is mainly intended to provide the required strength level (>1000MPa). However, such microstructures of hot-formed products can only provide a maximum total elongation of about 6%. Although the single-phase martensitic microstructure can provide good bendability (e.g. >100° for 1000MPa level and about 50° for 1500MPa level), the impact energy absorption capacity in these products is low due to the low total elongation. A method for manufacturing ultra-high-strength uncoated steel is known from US2016 / 0312323A1. The known method comprises the steps of providing an iron-based alloy comprising carbon and more than 2.5 wt. % manganese, annealing the iron-based alloy at a first temperature to form an annealed alloy, hot forming the annealed alloy at a second temperature to form a critical or austenitic structure and cooling the austenitic alloy thus annealed to form the ultra-high strength steel. In one embodiment, the annealed alloy is subjected to hot forming in the critical annealing temperature range. In another embodiment, the hot forming temperature is in the austenitizing annealing range. The soaking time is from about 1 minute to about 10 minutes. In this example, after a continuous annealing step of the cold rolled sheet, a thermal cycle of hot forming is simulated without causing actual deformation. It does not describe a method of continuous annealing and a method of applying any coating on the steel strip. EP18155866 discloses a method for hot forming a steel blank coated with Zn or a Zn alloy containing more than 3.1 wt. % Mn using a soaking time of only 3 minutes at most. It neither discloses a method for coating a steel strip with Zn or a Zn alloy nor does it take into account soaking times exceeding 3 minutes during reheating. Longer soaking times are preferred for steels containing relatively large amounts of Mn for efficient diffusion.
[0006] It is an object of the present invention to provide galvanic protection in connection with hot press formed steel strip products provided by a zinc based coating for (ultra) high strength steels while reducing the risk of (micro)cracking.
[0007] Another object of the present invention is to provide a hot dip galvanizing process which enables coating of steel strip containing a large amount of Mn with Zn or a Zn alloy while providing a continuous annealing process which provides the required microstructure for achieving high ductility in the final product.
[0008] Another object of the present invention is to provide a hot-dip zinc or zinc alloy coated steel product having high strength and high deformability at room temperature by hot press forming.
[0009] Therefore, the method according to the invention is a method for hot press forming a steel product from a zinc or zinc alloy coated steel strip, wherein the steel strip has the following composition in wt. %:
[0010] C: 0.05-0.3;
[0011] Mn: 3.0-12.0;
[0012] Al: 0.04-3.0;
[0013] Optional one or more other alloying elements:
[0014] Si: less than 1.5;
[0015] Cr: less than 2.0;
[0016] V: less than 0.1;
[0017] Nb: less than 0.1;
[0018] Ti: less than 0.1;
[0019] Mo: less than 0.5;
[0020] Unavoidable impurities, such as
[0021] S: less than 30 ppm by weight;
[0022] P: less than 0.04;
[0023] The balance is Fe;
[0024] The method for manufacturing the steel strip comprises the following steps:
[0025] - casting molten steel into slabs;
[0026] - reheating the slab to a temperature above 1150° C. and keeping it at said temperature for a period of 60 minutes or more;
[0027] - hot rolling the steel into strip, preferably with an exit hot finishing temperature FRT above the Ar3 temperature, wherein Ar3 denotes the temperature at which the ferrite transformation in the steel begins during cooling;
[0028] - coiling the hot rolled steel strip;
[0029] - pickling the hot rolled steel strip;
[0030] - optionally cold rolling the pickled hot rolled steel strip into a cold rolled steel strip, wherein in the case of cold rolling the hot pressed strip after coiling and pickling is subjected to a batch annealing at a temperature TB for a period PB, TB and PB being selected so that the steel has a microstructure exhibiting more than 60% by volume of ferrite after cooling to room temperature, wherein in a preferred embodiment TB and PB are selected wherein TB is 650° C. or less and PB is 24 hours or more;
[0031] - continuously annealing the strip according to an annealing thermal cycle, wherein the temperature of the steel strip is increased in a heating section, preferably at a rate of 1-15°C / s, and then maintained at a relatively stable level in a soaking section for soaking, wherein the soaking atmosphere is maintained at a temperature between TMIN and TMAX, wherein TMIN=TMAX-100°C, wherein the continuous annealing is considered to be terminated at a point in the heating cycle where the temperature of the steel strip decreases (preferably at a rate of 0.5-10°C / s):
[0032] - wherein TMAX is equal to or less than the lowest temperature of Ac3-100°C and 700°C;
[0033] - wherein the homogenous atmosphere has a dew point of -40 to -10°C;
[0034] - wherein the continuous annealing comprises pre-oxidizing the steel strip in the heating section in an annealing atmosphere having an oxygen content of 500 to 3000 ppm by volume;
[0035] - wherein the soaking atmosphere is a reducing atmosphere, preferably containing 1-15% by volume of hydrogen in nitrogen;
[0036] - wherein the continuous annealing time is 150 seconds or longer, preferably 180 seconds or longer, and the continuous annealing time consists of the time in the heating section plus the time in the soaking section;
[0037] - hot dip coating the steel strip with zinc or a zinc alloy while:
[0038] - Use an immersion time of 3 seconds or more;
[0039] - maintaining a bath temperature of 420°C to 500°C in a hot dip bath;
[0040] - wherein the zinc bath contains essentially zinc, at least 0.1 wt. % Al and optionally up to 5 wt. % Al and optionally up to 4 wt. % Mg, the balance of the bath comprising other elements each individually less than 0.3 wt. %, and unavoidable impurities;
[0041] -Hot pressing to form the product, comprising the following steps:
[0042] - providing a blank taken from the hot-dip zinc or zinc alloy coated steel strip;
[0043] - reheating the blank to a blank temperature TRH in the range of Ac3-300°C to 750°C,
[0044] - soaking the billet at TRH for a time longer than 3 minutes and at most 15 minutes;
[0045] - Transfer the blank to the press within 30 seconds;
[0046] - forming the article in the press, thereby cooling the article;
[0047] - Removing the article from the press.
[0048] Steel with a specific composition is processed into hot rolled strip or cold rolled strip by using a specific manufacturing process. Subsequently, the strip is continuously annealed using the temperature and duration of the treatment as well as the dew point and atmosphere in different stages of the process, thereby preventing surface enrichment of alloying elements of the steel and obtaining a surface suitable for good adhesion of the Zn or Zn alloy coating to the steel substrate by hot dip galvanizing. The prescribed continuous annealing process is carried out at a low critical temperature equal to or lower than the lowest value of Ac3-100°C or 700°C for the occurrence of Mn partitioning between the ferrite and austenite phases of the steel, which enables the formation of the desired microstructure with a large amount of retained austenite after hot press forming. Subsequently, the Zn or Zn alloy coated steel strip in the form of a blank is reheated in the same critical temperature zone (from Ac3-300°C to 750°C, preferably to 700°C) for more than 3 minutes, so that effective Mn partitioning between ferrite and austenite can occur again. The reheating temperature of the blank is selected in such a way that grain boundary penetration of liquid Zn or Zn alloy does not occur, minimizing surface microcracks during hot forming of the steel product. Preferably, in a hot-dip zinc or zinc alloy coated hot press formed steel comprising a steel substrate provided with a hot-dip coating layer, the length of any microcracks in the steel substrate is 5 μm or less.
[0049] For steels containing 3 to 12 wt. % Mn (conventionally denoted "medium Mn steels"), a well-adhering Zn or Zn alloy coating can be applied to the strip surface by hot-dip galvanizing.
[0050] The steel is subjected to continuous annealing at a critical temperature effective to partition Mn between the ferrite and austenite phases of the steel just before hot dipping the steel into a bath of Zn or Zn alloy. This feature facilitates Mn partitioning during subsequent reheating of the Zn or Zn alloy coated steel for hot press forming to provide the desired final microstructure with a high amount of retained austenite.
[0051] Reheating the Zn or Zn alloy coated steel billet to a temperature in the temperature range of Ac3-300°C to 750°C, preferably to 700°C minimizes the formation of liquid Zn or Zn alloy and its penetration into the grain boundaries of the steel substrate within a reheating duration equal to or exceeding 3 minutes.
[0052] The above reheating selected from the critical temperature range of the steel also ensures that the Mn pre-partitioning between ferrite and austenite that occurred during the previous continuous annealing process further occurs. A reheating time longer than 3 minutes results in a more effective partitioning of Mn, making the thermal stability of the austenite phase higher and obtaining a high retained austenite fraction after the product is cooled to room temperature.
[0053] In one embodiment of the method, the Mn content of the steel is 6.0 wt% or more. As explained below, this achieves the effect of substantially suppressing the Ac3 temperature of the steel. As a result, less Zn-rich liquid phase is formed during reheating of the billet and hot press forming. This suppresses zinc-induced liquid metal embrittlement and minimizes microcracks in the hot formed product. In addition, the lower required reheating temperature achieved by this preferred embodiment also saves energy costs during hot press forming and results in less oxidation of the zinc coating on the steel surface. As a result, the weldability of the hot formed product is improved and the necessity of sandblasting the product after hot forming is eliminated.
[0054] In one embodiment of the method, the slab is reheated to a temperature above 1200° C. or preferably above 1250° C. and maintained at said temperature for a period of 60 minutes or more. This achieves the effect of uniform distribution of Mn in the as-cast steel slab.
[0055] In another embodiment of the method, the slab is reheated to a certain temperature and kept at said temperature for a period of 120 minutes or more. This has the effect of obtaining an even more uniform distribution of Mn in the as-cast steel slab, minimizing any microsegregation.
[0056] In another embodiment of the method, TRH is in the range of Ac3-300° C. to 700° C. This achieves the effect of forming a minimum amount of zinc-rich liquid phase on the steel surface, reducing the chance of liquid phase penetrating into the steel substrate, thereby further minimizing or eliminating zinc-induced liquid metal embrittlement and microcracking phenomena.
[0057] In yet another embodiment of the method, the blank is transferred to the press within 10-15 seconds. This achieves the effect of minimizing the temperature loss of the steel blank, so that the product can be formed more easily, and the springback in the formed product can be minimized or eliminated.
[0058] The present invention is also embodied in a hot-dip zinc or zinc alloy coated hot press formed steel product obtainable by the method according to any one of claims 1 to 5, having a microstructure comprising the following components in volume %:
[0059] Ferrite: 30% or more, preferably 40% or more;
[0060] Retained austenite: 20% or more, preferably 30% or more;
[0061] Martensite: 40% or less, preferably 30% or less, including 0%.
[0062] High levels of ductility, expressed as total elongation and bendability, are achieved with such steel product microstructures containing 20% by volume or more, preferably 30% by volume or more, of retained austenite in combination with given amounts of ferrite and martensite. These microstructures also ensure that high strength values are achieved in the product, in particular due to the retained austenite that is transformed into strong martensite during cold deformation (such as in a crash), and due to any initial martensite present in the microstructure of the product.
[0063] In one aspect of the present invention, the hot-dip zinc or zinc alloy coated hot-pressed steel product has the following mechanical properties: yield strength ≥ 800 MPa, ultimate tensile strength ≥ 820 MPa, total elongation ≥ 10%, bending angle ≥ 80° at 1 mm thickness. Such products are particularly suitable for automotive applications, such as front or rear longitudinal bars, B-pillar lower parts, bumper beams, etc. Due to the high mechanical properties (i.e. total elongation, bendability and strength values), high collision energy absorption can be achieved in the product.
[0064] The present invention is based on modification of the composition of a steel substrate having a zinc or zinc alloy based coating, a processing route design that allows the steel to be put into cold and / or hot rolled form, a continuous annealing and hot dip galvanizing process design that makes the steel suitable for coating with Zn or Zn alloy and induces microstructural changes in the steel substrate that are beneficial for subsequent hot stamping, and a hot stamping process design.
[0065] The essential elements for steel substrate modification are Mn, C and Al. As the Mn content in the steel increases, the austenite transformation temperature (austenite transformation start (Ac1) and completion (Ac3)) decreases when heated. This enables annealing of the steel at a lower temperature in the critical phase region of the steel.
[0066] Suppressing the austenite transformation temperature has the following advantages:
[0067] Due to the low soaking temperature, the diffusion of alloying elements and the subsequent external selective oxidation of alloying elements is reduced. It should be mentioned that due to the increased Mn content in the steel substrate, there is a greater possibility of external selective oxidation of Mn, which will hinder the wettability of liquid zinc.
[0068] The reheating of the Zn or Zn alloy coated steel billet can also be carried out at a relatively low temperature, thereby minimizing the growth of thick oxides, ie more metallic zinc remains.
[0069] The hot press forming temperature is also lowered. This minimizes the formation of liquid zinc and its penetration into the grain boundaries and greatly reduces micro cracks caused by zinc.
[0070] The steel substrate is annealed and reheated within its critical temperature range to achieve the desired microstructure components, thereby ensuring high mechanical properties. This metallurgical requirement also contributes to the present invention. If the steel is annealed and / or reheated for hot forming at a temperature higher than Ac3 (i.e., in the austenite temperature), the desired microstructure cannot be obtained. If these heat treatments are performed at a temperature higher than the Ac3 temperature of the steel, a single phase of austenite will exist at the soaking temperature, and the composition of the austenite will present the overall composition of the steel with low thermal stability. On the other hand, when soaking is performed at the critical annealing temperature, the two phases of austenite and ferrite coexist at the soaking temperature. This allows alloying elements to be distributed between austenite and ferrite. The steel of the present invention contains Mn, C and Al as necessary alloying elements. Therefore, Mn and C will be distributed more in austenite because they are gamma-genic elements, and Al will be distributed more in ferrite because it is alpha-genic elements. In addition, the low heat treatment temperature ensures that the grain size of the steel remains fine. Due to the subcritical heat treatment, an ultrafine microstructure (≤2 μm grain size) is obtained, which improves the strength and ductility of the product.
[0071] Another importance of steel modification is as follows.The Mn amount increased in the steel, in the range of 3 to 12 weight %, will cause Mn to be enriched in austenite in a large number by the partitioning process in annealing and reheating process under the critical temperature range.This Mn enrichment has improved the thermal stability of critical austenite together with carbon enrichment.Therefore, in the process of cooling or quenching to room temperature, critical austenite will not be converted into martensite or any other phase to a great extent, so that a large amount of austenite (>20 volume %) can be retained in the microstructure of steel at room temperature.In the loading process, retained austenite is converted into martensite, causing transformation induced plasticity (TRIP) effect.Due to the TRIP effect, it improves processing or strain hardening rate, therefore high strength, high elongation and high bendability are realized in the product. A Mn content above 12 wt. % will make the steel difficult to continuously cast due to extreme segregation and the mechanism of plasticity enhancement will change from TRIP to TWIP (twin induced plasticity), while a content below 3 wt. % will not provide sufficient Mn enrichment in austenite for obtaining a sufficient amount of retained austenite at room temperature.
[0072] Similar to the effect of Mn described above, C is also enriched in critical austenite, improving the thermal stability of austenite and leading to austenite stabilization at room temperature microstructure. However, C is effective in an amount less than Mn, so the C content range for changing the chemical properties of steel in the present invention is 0.05 to 0.3 wt%. If the C content is less than 0.05 wt%, sufficient austenite stabilization effect cannot be obtained, and a C content above 0.3 wt% will make it difficult to post-process the prepared product (such as spot welding). Welding is a necessary step for assembling automotive parts into the body, so it is a very important aspect to consider. In the present invention, C is also added to the steel to increase strength.
[0073] Aluminum is not an austenite stabilizing element in steel, but a ferrite stabilizing element. However, in order to expand the critical temperature range of steel (Ac1 to Ac3), 0.04-3 wt. % is added to the steel. In the case of high levels of Mn, the steel becomes sensitive to small changes in processing temperature, and the resulting microstructure may change, resulting in variable mechanical properties. The addition of Al ensures the process robustness of the steel, so that the annealing and reheating temperatures of the steel can be selected with small changes to achieve the desired mechanical properties. When Al is not present in the steel except for the minimum level required for steel deoxidation (i.e., <0.04 wt. %), a more precise furnace needs to be used, but the present invention can still be carried out. The maximum amount of Al is limited to 3 wt. % to reduce the formation of oxide scale during hot rolling and the rolling force during hot and cold rolling.
[0074] In order to make the steel into hot and / or cold rolled strip, unique processing steps must be adopted in the present invention because the steel contains relatively large amounts of alloying elements, especially Mn. When the Mn content exceeds about 2% by weight, Mn has a tendency to segregate after casting. This will hinder product performance by providing uneven properties and may also cause cracking. Therefore, the cast slab must be fully homogenized. This is achieved by subjecting the slab to a relatively high temperature of more than 1150°C, preferably more than 1200°C, and for a sufficiently long time, preferably for 60 minutes or more.
[0075] Subsequently, due to the high alloying, the rolling forces are high during hot rolling of the strip. Hot rolling of the steel can be performed by using relatively high temperatures in the austenitic temperature range. The finishing temperature (FRT) is kept well above the Ar3 temperature, which can be above 900°C, to keep the required hot rolling forces relatively low.
[0076] In addition, when cold rolling is optionally applied to the hot rolled strip to reduce the specifications of the final steel product, it will not be possible to cold roll the material unless appropriate pretreatment is used. In particular, after hot rolling, the coiled steel is subjected to a batch annealing treatment preferably for 24 hours or more at a relatively low temperature within the critical temperature region of the steel. This batch annealing temperature should preferably be lower than 650°C, because at temperatures above this temperature, a large amount of retained austenite will be formed after the steel is cooled to room temperature. In addition, if a high batch annealing temperature is used, a large amount of martensite may appear in the microstructure. Both martensite and retained austenite make cold rolling difficult by increasing the rolling force. When the martensitic phase is hard, during the cold rolling process, the retained austenite itself is transformed into hard martensite, which increases the rolling force. Therefore, it is desirable to batch anneal the coiled material for maintaining the content of retained austenite and martensite at a relatively low value and increasing the amount of ferrite. The ferrite phase does not produce as much work hardening as the retained austenite during the cold rolling process, and thus the rolling force is kept low, making cold rolling possible.
[0077] Next, during the processing of the steel, the present invention requires designing the continuous annealing process in such a way that during the continuous annealing process, the steel surface remains clean and free of oxides to make it suitable for the subsequent hot-dip galvanizing step. The continuous annealing and hot-dip galvanizing steps of the present invention are schematically shown in Figure 1 The challenge is that in addition to producing a steel surface suitable for good Zn or Zn alloy adhesion, the continuous annealing treatment must also provide a steel substrate microstructure in which sufficient partitioning of Mn and C between ferrite and austenite occurs, resulting in a high retained austenite fraction in the substrate before reheating during hot press forming. In order to achieve these two requirements, the maximum soaking temperature TMAX during the continuous annealing process is kept below the lowest of Ac3-100°C and 700°C. This temperature is within the critical temperature range of steels optimized to obtain maximum partitioning of Mn into austenite. Regardless of the steel chemistry of the present invention, temperatures above 700°C will lead to severe external selective oxidation of the steel surface. Sufficient partitioning of Mn from ferrite to austenite is ensured by soaking times of at least 150 seconds, preferably more than 180 seconds. Shorter soaking times do not lead to sufficient Mn enrichment in austenite to impart sufficient thermal stability to it, because Mn is a relatively large substitutional alloying element that diffuses slowly in steel. On the other hand, carbon, as a small interstitial alloying element in steel, diffuses faster than Mn. Therefore, the requirement for minimum soaking time is mainly based on the diffusion coefficient of Mn rather than the diffusion coefficient of C. Heating rates of 1 to 15°C / s to the soaking temperature are preferred. Slower heating rates would make continuous annealing production less economically attractive, while faster rates would make the operation of a continuous annealing line extremely dangerous and therefore impractical.
[0078] In addition to maintaining the above-mentioned low soaking temperature during the continuous annealing process, the annealing atmosphere must also be controlled so that the steel substrate surface can have good adhesion of Zn or Zn alloy during hot dip galvanizing. Thus, during the heating of the steel strip to the soaking temperature, the annealing atmosphere is kept oxidizing, and the oxygen content in the annealing atmosphere is usually 500 to 3000 weight ppm. Due to this pre-oxidizing atmosphere, internal selective oxidation occurs and a thin wüstite layer is formed. Subsequently, during the soaking of the steel substrate at the annealing temperature, a reducing atmosphere preferably containing 1 to 15 volume % H2 is maintained in the annealing atmosphere. Due to the reducing atmosphere during the soaking process, wüstite is reduced. At the soaking temperature of the present application, the diffusion rate of the alloying elements is low, so the enrichment of the alloying elements is slow. An oxygen content of less than 500 weight ppm during the heating process will allow Mn and Si atoms to be oxidized on the steel surface, ultimately resulting in poor wetting of liquid zinc. On the contrary, an oxygen content of more than 3000 weight ppm will lead to excessive oxidation of Fe, resulting in the formation of a thick FeO layer on the steel surface. This surface is not suitable for Zn or Zn alloy adhesion. In addition, these FeO particles may stick to the roller during the production process, resulting in a large number of surface defects.
[0079] After ensuring that the surface of the steel substrate is free of the above-mentioned alloying elements enrichment during the continuous annealing process, the steel strip is immersed in a bath containing liquid Zn or Zn alloy maintained at a temperature between 420°C and 500°C. Below a bath temperature of 420°C, Zn will remain in a solid state, and above 500°C, excessive evaporation of the liquid Zn or Zn alloy will occur. Typical temperatures optimized for the viscosity of the liquid and its evaporation are in the range of 450-465°C. In addition, the duration of immersion of the steel strip in the Zn or Zn alloy liquid bath is also important. This duration is determined by the speed at which the steel strip passes through the continuous annealing line. The line speed in the continuous annealing facility should be adjusted in such a way as to ensure a minimum immersion duration of 3 seconds for the steel strip in the galvanizing bath. In order to obtain good adhesion between the steel strip and the Zn or Zn alloy, a time of 3 seconds or more is necessary.
[0080] The above hot dip galvanizing conditions apply to a Zn bath containing essentially zinc, at least 0.1 wt. % Al and optionally up to 5 wt. % Al and up to 4 wt. % Mg, the remainder of the bath comprising less than 0.3 wt. % of other elements each individually, and unavoidable impurities. Thus, the present invention is not limited to pure Zn coatings, but can be applied to a variety of Zn-based coating variants.
[0081] The invention relating to hot press forming of a steel substrate and its processing into a coated strip operates in conjunction with a hot forming method which is also part of the invention. The hot forming cycle is schematically shown in Figure 1Right hand side. According to the invention, for hot pressing of Zn or Zn alloy coated steel strip or billet, reheating at low temperature is necessary in the critical temperature region of the specially designed steel substrate. The typical temperature range for reheating, TRH is Ac3-300°C to 750°C, preferably to 700°C.
[0082] The choice of this temperature range was based on several considerations:
[0083] - No need for complete austenitization;
[0084] - The hot-formed parts of the present invention do not need to be sandblasted to remove Zn oxides before welding like conventional hot-formed steels, because the zinc oxide present after heat treatment is still very thin. This reduces the manufacturing cost of hot-formed parts by eliminating the cost of sandblasting and improving spot weldability;
[0085] - The basic features of the microstructure of the steel substrate of the present invention do not change significantly during the hot press forming process. Therefore, the pressing temperature can be lower than in the case of conventional hot press forming. In this way, the metal embrittlement caused by zinc can be minimized. When the formation of microcracks is minimized during the hot forming process, the product achieves high fatigue resistance and durability.
[0086] Due to the above-mentioned low temperature reheating, oxidation of the Zn or Zn alloy coating is also minimized, and the metal coating remains relatively thick, which provides good galvanic protection to the steel substrate in terms of performance, thereby improving the corrosion resistance of the product.
[0087] The above benefits arising from the selection of low reheating temperatures during hot forming are related to Zn or Zn alloy coatings on steel substrates. This selection of the billet reheating temperature is also intended to facilitate the formation of the correct microstructure in the steel substrate to achieve the desired mechanical properties and final mechanical performance. As previously mentioned, due to the selection of the soaking temperature within the critical temperature range of the steel substrate, the substrate has already formed a large amount of retained austenite in the previous continuous annealing step. Critical reheating for hot forming supplements this by further promoting the partitioning of Mn and C into austenite, so that retained austenite with higher mechanical stability can be obtained in the hot formed steel substrate. This reheating step will also produce an additional amount of retained austenite due to the additional opportunity for the diffusion of austenite stabilizing elements into the critical austenite.
[0088] The thus reheated blank is transferred to a forming tool for deformation, typically a press, in which the blank is deformed to a desired shape. The transfer time is preferably within 30 seconds, more preferably within 10-15 seconds to avoid overcooling of the blank. After forming in the press, the product is cooled. Because the critical austenite with a high Mn amount is very stable, and when it is partially converted into martensite, it has extremely high hardenability, so that a higher rate of die quenching is not required, so the die quenching that is essential in traditional hot forming is not necessary in the present invention. The shaped product can be taken out from the press and cooled in an ambient atmosphere. It is also possible to (force) cool in air with forced air cooling or in combination with die quenching.
[0089] The reheated blank is transferred from the furnace or other heating device to the forming tool for deformation. As mentioned, it is preferred that the transfer time is short, preferably within 10-15 seconds. In an advantageous embodiment, the temperature drop of the steel blank during the transfer does not exceed 150°C. Preferably, the temperature drop is in the range of 100-150°C. If the temperature drop is higher, the blank may be too strong to be deformed in the subsequent forming step.
[0090] Furthermore, the present invention allows the shaped article to be removed from the thermoforming press immediately after forming, for example at an exit temperature in the range of 100-450°C, such as 200-425°C, since press quenching is not strictly necessary.
[0091] In one embodiment, the cooling step is carried out in a press, advantageously to a temperature of 100-250° C., preferably 150-200° C. A cooling rate of at least 3° C. / s is suitable in view of the hardenability of the modified steel substrate. Even this relatively slow cooling rate will ensure that austenite is transformed again into martensite in the shaped article. Advantageously, the quenching rate is at least 5° C. / s. After removal from the press, the shaped article is further cooled to ambient temperature.
[0092] The key to achieving this mechanical property in the present invention is the process chain of the modified steel substrate chemistry described above, which results in a unique microstructure in the final hot forming condition. The steel chemistry modified with the processing of the present invention obtains at least 20% by volume of retained austenite and at least 30% by volume of ferrite, while martensite is 40% by volume or less, including 0% by volume. This relatively high fraction of retained austenite is metastable and provides a TRIP effect to achieve a combination of high strength, elongation and bendability, resulting in high crashworthiness of hot-formed hot-dip galvanized or zinc alloy coated steel products. Even when the retained austenite is relatively stable, its inherent ductility higher than ferrite and martensite provides high ductility values due to its face-centered cubic (FCC) crystal structure.
[0093] The steel used in the method according to the invention is an inventive steel concept comprising carbon, manganese and aluminium as main components. Optionally, other alloying elements selected from silicon, chromium, vanadium, niobium, titanium and molybdenum may be present. Unavoidable impurities such as N, P, S, O, Cu, Ni, Sn, Sb etc. (derived from the raw materials used to prepare the steel composition) may be present, but in very low concentrations. They are not deliberately added or specifically controlled within predetermined limits. The balance of the steel composition is iron.
[0094] Carbon is present in an amount of 0.05-0.3 wt%, preferably 0.05-0.25 wt%, more preferably 0.08-0.2 wt%. It is added primarily for strength, although carbon also helps stabilize austenite. In the present composition, the austenite stabilizing effect of manganese is much more pronounced due to its higher proportion. Too little C will not provide the required strength level of 820 MPa or more, preferably 1000 MPa or more, and if C is above 0.3, the weldability of the formed part may deteriorate.
[0095] Manganese is present in an amount of 3.0-12.0 wt %. Manganese reduces Ac1 and Ac3 temperatures, stabilizes austenite, improves strength and toughness, and induces the TRIP effect by stabilizing austenite at room temperature microstructure. At levels below 3.0 wt %, the target effect cannot be achieved, and at amounts above 12.0 wt %, problems in casting and segregation will be caused. Moreover, the deformation mechanism will change from transformation induced plasticity (TRIP) to twin induced plasticity (TWIP). If the Mn content is too low, the residual austenite at room temperature is insufficient and the stability of the retained austenite is too low, resulting in the inability to obtain ductility benefits. Preferably, the Mn content is 3.5-10.5 wt %. In one embodiment, the amount of Mn is 5.0-9.0 wt %. In other embodiments, it is 5.5-8.5 wt %, such as 6.0-7.5 wt %.
[0096] Aluminum may be added to extend the temperature range Ac1-Ac3 for increasing the robustness of the process in terms of industrial applications.Al is present in an amount of 0.04-3.0 wt%, preferably 0.5-2.5 wt%, more preferably 1.0-2.2 wt%.
[0097] If present, silicon is added in an amount less than 1.5% to improve strength by solid solution strengthening. If present, the amount is generally greater than 0.01% by weight and less than 1.5% by weight. The preferred range is 0.1-1.0% by weight.
[0098] Both Al and Si help to suppress cementite precipitation to avoid ductility degradation. In addition, Al and Si also increase the peak annealing temperature for obtaining the maximum amount of retained austenite at room temperature. Therefore, during intercritical annealing, the diffusion of Mn is beneficial to the effective partitioning of Mn in austenite.
[0099] Optionally, one or more other microalloying elements selected from V, Nb, Ti and Mo are present. These microalloying elements improve strength by precipitation hardening of their carbides, nitrides or carbonitrides. Cr, another optional element of the present invention, also increases the peak annealing temperature for obtaining a maximum amount of retained austenite at room temperature and reduces the sensitivity of the retained austenite content to the annealing temperature. These result in an effective partitioning of Mn in the austenite and improved process robustness during annealing. If present, the preferred addition amounts of these optional alloying elements are: V: 0.01-0.1 wt. %; and / or Nb: 0.01-0.1 wt. %; and / or Ti: 0.01-0.1 wt. %; and / or Mo: 0.05-0.5 wt. %; and / or Cr: 0.1-2.0 wt. %.
[0100] There is no restriction on the composition of the zinc or zinc alloy coating. Hot dip coating can be carried out using a standard GI coating bath, where GI stands for "normal galvanizing, i.e. hot dip coating using a bath containing mainly zinc". Several Zn coating baths can be applied, such as a zinc bath containing essentially zinc, at least 0.1 wt% Al, and optionally up to 5 wt% Al and optionally up to 4 wt% Mg, the remainder of the bath containing other elements each individually less than 0.3 wt%, and unavoidable impurities. The zinc alloy coating can be realized as containing 0.3-4.0 wt% Mg and 0.05-6.0 wt% Al and optionally up to 0.2 wt% of one or more additional elements and unavoidable impurities, and the balance is zinc. For example, in order to form zinc flowers and / or prevent scum formation, the additional elements that can be present in a small amount of less than 0.3 wt% can be selected from Pb, Sb, Ti, Ca, Mn, Sn, La, Ce, Cr, Ni, Zr and Bi. Pb, Sn, Bi and Sb are preferred. For common applications, small amounts of such additional elements do not significantly change the properties of the bath or the resulting coating. Preferably, when one or more additional elements are present in the coating, each additional element is present in an amount <0.02 wt%, preferably each is present in an amount <0.01 wt%.
[0101] The obtained hot-dip zinc or zinc alloy coated hot press formed steel product preferably has a triple or dual microstructure comprising (in volume %):
[0102] Ferrite: 30% or more, preferably 40% or more;
[0103] Retained austenite: 20% or more, preferably 30% or more;
[0104] Martensite: 40% or less, including 0%, preferably 30% or less, including 0%.
[0105] Advantageously, the resulting shaped articles have the following properties:
[0106] Yield strength: 800 MPa or higher; preferably 850 MPa or higher, more preferably 900 MPa or higher
[0107] Tensile strength: 820MPa or higher; preferably 1000MPa or higher
[0108] Total elongation: 10% or more; preferably 15% or more, more preferably 25% or more
[0109] Minimum bending angle at 1.0 mm thickness: 80° or more; preferably 90° or more.
[0110] The above phase fractions are determined by using X-ray diffraction (XRD). The amount of retained austenite is determined by XRD at the 1 / 4 thickness position of the sample. The XRD pattern is recorded in the range of 45 to 165 ° (2θ) on a Panalytical Xpert PRO standard powder diffractometer (CoKa-radiation). The quantitative determination of the phase ratio is performed by Rietveld analysis using a Bruker Topas software package for Rietveld correction. The martensite content is determined by the peak at the ferrite diffraction position in the diffraction pattern. The grain size of this phase can be determined by a scanning electron microscope image of the microstructure.
[0111] The yield strength, ultimate tensile strength and total elongation were measured by quasi-static (strain rate 3×10 -4 s -1 ) tensile test. The geometry of the tensile specimens included a 50 mm gauge length, a 20 mm width and a nominal thickness of 1.5 mm in the rolling direction. Bendability was determined in the longitudinal and transverse directions by a three-point bending test in accordance with VDA 238-100 standard on a nominal 1.5 mm thick, 40 mm x 30 mm specimen. The bending axis had a dimension of 30 mm and a bending radius of 0.4 mm. The bending angle obtained from the nominal 1.5 mm specimen was converted to an angle corresponding to a thickness of 1.0 mm using the following formula: Bending angle at 1.0 mm thickness = measured angle x square root of actual thickness in millimeters. From these converted bending angles, for specific heat treatment conditions, the lowest values for the longitudinal and transverse specimens are considered to be within the scope of the present invention.
[0112] By using a critical continuous annealing step in the production of steel strip as described above before reheating the blanks cut from the strip, a Mn partitioning from ferrite to austenite occurs, making the critical austenite even more stable. During cooling after critical annealing via hot-dip galvanizing, the critical austenite does not significantly transform into martensite due to its high stability and due to the low Ms (i.e. high thermal stability), resulting in a triple (ferrite + retained austenite + martensite) or dual (ferrite + retained austenite) microstructure. For high Mn contents, for example above 10.5 wt.%, a fully dual structure can be obtained, and for Mn contents below 10.5 wt.%, a triple structure is formed. In addition, by increasing the Mn content, a low reheating temperature TRH (for example below 700° C.) and a high amount of retained austenite (20 volume % or more) can be ensured. This high amount of retained austenite is fully or partially transformed into martensite during deformation, leading to a transformation induced plasticity (TRIP) effect, resulting in a high strain hardening rate (= high elongation and high strength).
[0113] When the steel strip is intercritically annealed at a temperature below 700°C (using a continuous annealing process step), the strip has high strength and high ductility due to the presence of a large amount of retained austenite. During the reheating process for hot forming in the intercritical temperature range, also below 750°C or preferably below 700°C, additional Mn partitioning can occur, providing austenite with higher stability. However, when the annealing and reheating temperatures are different, some redistribution of Mn can occur. This may in some cases lead to a slightly smaller amount of retained austenite after hot forming than after continuous annealing and hot dip galvanizing. However, a large amount of retained austenite (>20 volume %) is obtained that still allows the present invention to work. If present, the martensite can be slightly tempered, but this phenomenon will contribute to even higher elongation values.
[0114] Due to the steel composition and the strip annealing and billet reheating steps used, the residual elongation (or service ductility) of the product is preferably 25% or more. The method of intercritical annealing and intercritical reheating steps of medium Mn steel is preferably used to obtain a mixed microstructure of ultrafine ferrite (0.5-2.0 μm) and martensite with high retained austenite regions. Therefore, high ductility is obtained in the final product.
[0115] Preferred hot dip zinc or zinc alloy coated hot press formed steel products are automotive parts such as front / rear longitudinal bars or bumper beams, especially those requiring high energy absorption combined with high strength. Non-limiting examples include B-pillars and structural parts of the chassis.
[0116] The present invention will be explained with reference to the embodiments described below. With reference to the accompanying drawings, in which:
[0117] Figure 1Schematic diagram showing a continuous annealing-hot dip galvanizing cycle and a subsequent hot forming cycle;
[0118] Figure 2 Shown are (a) actual Ω-shaped profiles and (b) schematic locations of samples used for microcrack investigation after hot forming.
[0119] Three ingots of the chemical compositions A, B and C of the invention were cast with dimensions of 200 mm x 100 mm x 100 mm by melting the charge in a vacuum induction furnace. The chemical compositions of these steels are given in Table 1 together with the conventional 22MnB5 steel grade usually used for hot forming. The 22MnB5 steel grade was received in a GI coated condition with a thickness of 1.5 mm and further processed for comparison. The ingots of the steels A, B and C of the invention were reheated at 1250° C. for 2 hours and rough rolled to a thickness of 25 mm. Subsequently, the strip was reheated again at 1250° C. for 30 minutes and hot rolled to a thickness of 3 mm, with a final rolling temperature (FRT) of 900° C. for all three steels, which is in the austenite phase region. The transformation temperature (Ar3) of austenite to ferrite during cooling was measured by dilatometry to be 798, 805 and 725° C. for steels A, B and C, respectively. The hot rolled steel was subjected to coil cooling simulation in a muffle furnace from 680°C and cooled therefrom to room temperature. The hot rolled strip was then annealed in a muffle furnace at 600°C for 96 hours under protective atmosphere and air cooled to room temperature. The strip was then pickled in HCl acid at 90°C to remove oxides and cold rolled to a thickness of 1.5 mm using multiple passes.
[0120] The cold rolled strip of steel A was subjected to continuous annealing at 675°C for 5 minutes, while steels B and C were subjected to continuous annealing at 650°C for 5 minutes, after which all the steel strips were directly immersed in a galvanizing bath containing a Zn alloy (hot dip galvanizing) containing mainly Zn and 0.4 wt% Al. The dimensions of the strip were 200 mm×105 mm×1.5 mm. The bath temperature was maintained at 465°C with an immersion time of 5 seconds, after which the strip was cooled to room temperature at 5°C / second, similar to air cooling. These continuous annealing and hot dip galvanizing simulations were performed in a hot dip annealing simulator. The atmosphere during the soaking process of the continuous annealing part of the thermal cycle was set to NH5 gas with a dew point of -30°C and 5% by volume H2 gas. During the heating process (i.e., the early part of the continuous annealing), the atmosphere was varied at an air-fuel ratio (λ) of 0.98, 1.005, 1.01 and 1.02, with a fixed dew point of 20°C. It should be mentioned that when λ>1, the atmosphere is considered to be oxidizing, and when λ<1, the atmosphere is considered to be reducing. Figure 1 A schematic diagram of the continuous annealing-hot dip galvanizing cycle, followed by a hot press forming operation, is shown in FIG, and the oxygen content in the annealing atmosphere during the heating part of the continuous annealing for different λ values is summarized in Table 2.
[0121] The Zn coated strips were subsequently thermoformed using the thermal cycle shown in Table 4 in a thermoforming press supplied by Schuler SMG GmbH & Co. KG. Figure 1 The thermal cycle is also schematically shown in the right part of the diagram. Two types of tools for forming were used - a flat tool for obtaining tensile, bending, contact resistance, corrosion and microstructural specimens, and a hat-top tool for obtaining Ω-shaped profiles for microcrack studies ( Figure 2 (a)). Additional reheating time-temperature combinations were used for contact resistance and corrosion measurements, which are given in Tables 10 and 11, respectively.
[0122] Galvanized strips of 30 mm x 200 mm (rolling direction x transverse direction) dimensions were subjected to the Zn adhesion test adopted by the automotive industry. In this test, Betamate 1496V glue (at least 150 mm long, 4-5 mm thick and at least 10 mm wide) was applied to the center of the strip on both sides of the strip. The glue was then cured in an oven at 175°C for 30 minutes. The sample was then firmly clamped, glue side outwards, and bent at a moderate speed to an angle of 90° with a bending radius of 1.1 mm. The sample was then visually inspected and given a code describing the state of Zn delamination.
[0123] According to NEN10002 standard, 3×10 -4 s -1 Tensile tests were performed at a quasi-static strain rate of 1.50 mm. Tensile specimens with a gauge length of 50 mm and a width of 20 mm in the rolling direction were used. Three-point bending tests were performed on specimens of 40 mm x 30 mm x 1.5 mm with a bending radius of 0.4 mm (= punch radius) in the longitudinal and transverse directions according to VDA 238-100. The bending angles were converted to a sheet thickness of 1.0 mm using the formula described above.
[0124] The following are the abbreviations and symbols used in the tables to represent the results of the tensile and bend tests: Rp = yield strength, Rm = ultimate tensile strength, Ag = uniform elongation, A50 = total elongation for a 50 mm gauge length, BA = bend angle, L = longitudinal specimen with the bend axis parallel to the rolling direction, T = transverse specimen with the bend axis perpendicular to the rolling direction.
[0125] The amount of retained austenite was determined by X-ray diffraction (XRD) at the 1 / 4 thickness position of the sample. The XRD pattern was recorded in the range of 45 to 165 ° (2θ) on a Panalytical Xpert PRO standard powder diffractometer (CoKa-radiation). The quantitative determination of the phase ratio was performed by Rietveld analysis using a Bruker Topas software package for Rietveld correction. The martensite content was determined by the peak at the ferrite diffraction position in the diffraction pattern.
[0126] The microcracks of hot-formed Ω-shaped profiles were investigated. The dimensions of the Ω-shaped profiles and the scheme for the microcrack investigation are shown in Figure 2 From the Ω profile, sections 1 cm wide were cut along the height and the microcracks of the specimens in the cross section of the coated sheet were investigated using an optical microscope at 1000× magnification. For this purpose, a length of about 1 cm from the middle height of the profile to the base was examined.
[0127] The contact resistance of hot-formed blanks of steels B and D was measured under a wide range of time and temperature combinations (given in Table 10) without any sandblasting following the ISO 18594 standard to obtain an indication of the weldability of the hot-formed material. For the same reheating conditions, the corrosion resistance of the coated steels was also determined without any sandblasting. The corrosion tests of hot-formed steels B and D were carried out according to the VDA 621-415 standard. Each blank sample was phosphated and electroplated and then scribed. Wide and narrow scribes (1 mm and 0.3 mm wide, 100 mm long) placed in parallel were marked on the sample in the longitudinal direction. The distance between the two types of scribes was kept at 30 mm and the distance from the edge of the sample was kept at 35 mm. A solution of 5% by volume of NaCl + 10 g of NaHCO3 in 150 liters of H2O was used as the corrosion medium. The formation of red rust (Zn oxide) on the scribe was monitored over a period of several weeks and the percentage length of the scribe covered with red rust was taken as a measure of corrosion. The corrosion resistance and contact resistance measurements also included unreheated 22MnB5 steel specimens for comparison.
[0128] The results of the Zn alloy coating adhesion test are given in Table 3, with "P" (=pass) indicating the coating remained intact after the test and "F" (=fail) indicating the coating delaminated during the test. It can be seen that when λ was 0.98, i.e. when no oxygen was present in the heating section during the continuous annealing (see Table 2), the coating delaminated during the test for all three steels A, B and C. On the other hand, when λ values were 1.005 and 1.01 (corresponding to 800 and 1700 wt ppm oxygen contents in the heating section), all three coated steels passed the coating adhesion test. However, when λ value was 1.02 (=3700 wt ppm oxygen content in the heating section of the continuous annealing), the coating delaminated during the test in all three steels. These results indicate that during the heating process of the continuous annealing of the steel strip according to the invention, an optimized amount of oxygen content needs to be present for a good coating adhesion to the steel surface. For the absence of oxygen (λ=0.98), selective oxidation of Mn occurs at the surface of the steel, which cannot be reduced back to metallic Mn, and therefore the substrate surface will not be suitable for adhesion of Zn or Zn alloys during hot dipping. But when there is too much oxygen (λ=1.02) of 3700 wt ppm, too much Fe oxide forms a thick FeO layer on the steel surface. This surface is not suitable for adhesion of Zn or Zn alloys. In addition, these FeO particles may stick to the rollers during production, causing a large number of surface defects. The tensile properties of the steels in their hot-dip galvanized condition, i.e. before hot forming, are given in Table 5, and the corresponding steel substrate microstructures are given in Table 6 together with those of the as-received GI 22MnB5 steel grade (steel D). Due to the use of the critical annealing temperature for soaking during continuous annealing, a high fraction of retained austenite is obtained in all three inventive steels, together with the desired amount of ferrite and a small amount of martensite (Table 6). This is possible because the intercritical austenite is enriched with Mn and C during annealing, which increases the thermal stability of the austenite by lowering its Ms temperature. In contrast, the 22MnB5 steel grade, which has not been modified with any of the inventive chemical compositions and has not been continuously annealed with the goal of austenite stabilization, has a ferrite-pearlite microstructure without any retained austenite. The effect of the specific microstructures obtained in the inventive steels A, B and C is reflected in their mechanical properties (Table 5). These steels have much higher yield strength and tensile strength values, as well as good total elongation due to the increased strain hardening rate achieved by the TRIP effect of retained austenite. This benefit is also reflected in the higher Rm×A50 values of the inventive steels, which is an indicator of the energy absorption capacity of the steel.
[0129] The mechanical properties and corresponding microstructural compositions of all steels after hot press forming are presented in Tables 7 and 8, respectively. It is observed that in the steels of the invention, more than 30% by volume of retained austenite is obtained in their microstructures under all reheating conditions due to the partitioning of Mn (and C) into austenite during the intercritical reheating process. In steel B, the retained austenite content increases for any particular reheating temperature as the reheating time increases due to the partitioning of more Mn into austenite. In general, at higher reheating temperatures, the retained austenite content decreases slightly due to the partitioning of less Mn into austenite (this can also be shown by ThermoCalc calculations). In general, the retained austenite content in steels A, B and C after hot forming is similar or slightly higher than before hot forming (Tables 6 and 8). Therefore, it may seem that not much benefit is generated due to further Mn partitioning during hot forming. This is not the case, as can be clearly seen from the comparison (to be performed later) of the corresponding total elongation, tensile strength and product of total elongation and tensile strength (Tables 5 and 7). The conventional 22MnB5 steel grade produces a microstructure that is mainly martensite (98.3 volume %) after hot forming, compared to the >30 volume % retained austenite in the steel of the invention. The ferrite fraction in the steel of the invention exceeds 40 volume %, and the martensite fraction is less than 20 volume %.
[0130] Due to the desired microstructure formed in the steel of the present invention, attractive mechanical properties are obtained (Table 7). A total elongation of more than 20%, a yield strength of more than 800 MPa and an ultimate tensile strength of more than 950 MPa are achieved in the steel of the present invention. Due to the higher content of retained austenite, the steel containing a higher amount of Mn (steel C) also achieves higher ultimate tensile strength and total elongation than the steels containing lower Mn (steels A and B). After hot forming, the energy absorption values (Rm×A50 value) in the steel of the present invention are generally also high. Conventional 22MnB5 steel grade achieves a tensile strength of more than 1500 MPa, but has a much lower energy absorption capacity due to poor total elongation. The energy absorption capacity of the steel of the present invention is at least 2.5 times that of the 22MnB5 steel grade under all reheating conditions. In addition, the bending angle of the hot formed steel of the present invention at a thickness of 1.0 mm is much higher than that of 22MnB5. Steels A, B and C achieve a minimum bending angle of more than 100°. As mentioned above, these surprising mechanical properties of the inventive steel are due to the high fraction of retained austenite phase in its microstructure, which provides high work hardening due to the TRIP effect. The additional Mn enrichment in the austenite during reheating is reflected in the higher energy absorption values of the hot-formed inventive steel than in hot-dip galvanized steel.
[0131] The results of the microcrack study are provided in Table 9. After hot forming the steel of the present invention at low temperature, there were a small number of microcracks of short length. However, the GI 22MnB5 steel grade, conventionally hot formed at higher temperatures, showed a large number of long microcracks on its surface. This minimization of microcracks in the steel of the present invention is due to the low temperature reheating and hot forming, which minimizes zinc diffusion and penetration into the steel grain boundaries, inhibiting metal embrittlement during hot forming. However, for 22MnB5, the same benefit was not obtained due to the higher temperatures used.
[0132] The results of the contact resistance measurements are given in Table 10. It was observed that when the reheating temperature of the steel of the present invention (steel B) was up to 700°C for different soaking times up to 15 minutes, the contact resistance values were low, comparable to those of the as-impregnated GI 22MnB5 (steel D), and much lower than those of the GI 22MnB5 reheated at higher temperatures (800-900°C). It should be mentioned that the as-impregnated GI22MnB5 is weldable, so the low contact resistance values of the steel of the present invention after hot forming indicate that the steel is also weldable. However, the contact resistance values of steel B increased upon reheating at 800°C, indicating oxidation of the Zn or Zn alloy coating. This will affect the spot weldability of the hot formed part, so from the weldability point of view, the reheating temperature should be limited to 700°C or lower.
[0133] Similar trends in corrosion results were observed, which are given in Table 11. In the steel B of the invention, the formation of red rust increases slowly with the reheating temperature up to 700°C, followed by a sharp increase for a reheating temperature of 800°C. Up to 700°C, the percentage of red rust is low, although slightly higher than that of GI 22MnB5 in the as-impregnated state, indicating good corrosion resistance of this hot formed product. When hot formed at 900°C, the corrosion resistance is much higher than that of GI 22MnB5 (steel D). Therefore, these results indicate that the steel of the invention has a higher corrosion resistance due to its Zn or Zn alloy coating when the reheating temperature is limited to 700°C. Severe oxidation of the Zn-based coating at 800°C leads to a sharp drop in corrosion resistance.
[0134] Table 1: Composition of steel in wt %
[0135] steel C Mn Si Al P S B Cr Mo Ni Cu A 0.155 7.4 0.20 1.99 0.0012 0.0015 0.0001 0.004 0.001 0.004 0.03 B 0.13 6.9 0.20 2.02 0.0010 0.0018 0.0002 0.004 0.001 0.002 0.03 C 0.14 10.1 0.18 1.7 0.00010 0.004 0.0001 0.024 0.001 0.014 0.02 D 0.23 1.24 0.02 0.03 0.002 0.0008 0.003 0.01 0.001 0.001 0.03
[0136]
[0137] Table 2: Annealing atmosphere for steels A, B and C
[0138]
[0139] Table 3: Results of Zn adhesion test (F = Fail, P = Pass)
[0140] Lambda value in the heating section Steel A Steel B Steel C 0.98 F F F 1.005 P P P 1.01 P P P 1.02 F F F
[0141] Table 4: Reheating time and temperature
[0142]
[0143] Table 5: Mechanical properties of Zn coated blanks before hot forming
[0144]
[0145] Table 6: Microstructural composition of Zn-coated blanks before hot forming
[0146]
[0147] Table 7: Mechanical properties of steel after hot forming
[0148]
[0149]
[0150] Table 8: Microstructure composition of hot-formed steel
[0151]
[0152] Table 9: Analysis results of microcracks after hot forming
[0153]
[0154] Table 10: Contact resistance results
[0155]
[0156]
[0157] Table 11: Corrosion test results after 1 week of testing
[0158]
[0159]
Claims
1. A method for hot press forming a steel product from a zinc or zinc alloy coated steel strip, wherein the steel strip has the following composition in wt. %: C:0.05-0.3; Mn: 3.0-12.0; Al:0.04-3.0; Optional one or more other alloying elements: Si: less than 1.5; Cr: less than 2.0; V: less than 0.1; Nb: less than 0.1; Ti: less than 0.1; Mo: less than 0.5; Unavoidable impurities, including: S: less than 30 ppm by weight; P: less than 0.04; The balance is Fe; The method for manufacturing the steel strip comprises the following steps: - casting molten steel into slabs; - reheating the slab to a temperature above 1150° C. and keeping it at said temperature for a period of 60 minutes or more; - hot rolling the steel into strip; - coiling the hot rolled steel strip; - pickling the hot rolled steel strip; - optionally cold rolling the pickled hot rolled steel strip into a cold rolled steel strip, wherein in the case of cold rolling the hot rolled strip after coiling and pickling is subjected to a batch annealing at a temperature TB for a period PB, TB and PB being selected so that the steel has a microstructure exhibiting more than 60% by volume of ferrite after cooling to room temperature; - continuously annealing the strip, wherein the temperature of the steel strip is increased in a heating section and then maintained at a relatively stable level in a soaking section for soaking, wherein the soaking atmosphere is maintained at a temperature between TMIN and TMAX, wherein TMIN = TMAX - 100°C, wherein the continuous annealing ends at a point in the annealing where the temperature of the steel strip decreases: - wherein TMAX is equal to or less than the lower temperature of Ac3-100°C and 700°C; - wherein the homogenous atmosphere has a dew point of -40 to -10°C; - wherein the continuous annealing comprises pre-oxidizing the steel strip in the heating section in an annealing atmosphere having an oxygen content of 500 to 3000 ppm by volume; - wherein the soaking atmosphere is a reducing atmosphere, wherein the reducing atmosphere contains 1-15% by volume of hydrogen in nitrogen; - wherein the continuous annealing time is 150 seconds or longer, and the continuous annealing time consists of the time in the heating section plus the time in the soaking section; - hot dip coating the steel strip with zinc or a zinc alloy, while: - Use an immersion time of 3 seconds or more; - maintaining a bath temperature of 420°C to 500°C in a hot dip bath; - wherein the bath essentially contains zinc, at least 0.1 wt.-% Al and optionally up to 5 wt.-% Al and optionally up to 4 wt.-% Mg, the balance of the bath comprising other elements each individually less than 0.3 wt.-%, and unavoidable impurities; - hot pressing the product, comprising the following steps: - providing a blank taken from said hot-dip zinc or zinc alloy coated steel strip; - reheating the blank to a blank temperature TRH in the range of Ac3-300°C to 750°C, - soaking the blank at TRH for a period of 5 to 15 minutes; - Transfer the blank to the press within 30 seconds; - forming the article in the press, thereby cooling the article; - Removing the article from the press.
2. The method of claim 1, wherein in the step of hot rolling the steel into a strip, the exit hot rolling finish temperature FRT is higher than Ar 3 temperature, wherein Ar 3 represents the temperature at which ferrite transformation starts in the steel during cooling.
3. The method according to claim 1 or 2, wherein TB and PB are selected such that TB is 650°C or less and PB is 24 hours or more.
4. The method according to claim 1 or 2, wherein the temperature of the steel strip is increased at a rate of 1-15°C / s in the heating section.
5. The method according to claim 1 or 2, wherein the temperature drop rate of the steel strip is 0.5-10°C / s.
6. The method of claim 1 or 2, wherein the continuous annealing time is 180 seconds or longer.
7. The method of claim 1, wherein the Mn content is 6.0 wt% or more.
8. The method of claim 1 or claim 2, wherein the slab is reheated to a temperature above 1200°C and maintained at said temperature for a period of 60 minutes or more.
9. The method of claim 8, wherein the slab is reheated to a temperature above 1250°C.
10. The method of claim 1 or 2, wherein the slab is reheated to a temperature above 1150°C and maintained at said temperature for a period of 120 minutes or more.
11. The method of claim 1 or 2, wherein TRH is in the range of Ac3-300°C to 700°C.
12. The method of claim 1 or 2, wherein the blank is transferred to the press within 10-15 seconds.
Citation Information
Patent Citations
Ductile Ultra High Strength Medium Manganese Steel Produced Through Continuous Annealing and Hot Stamping
US20160312323A1
Method of shaping an article from a zinc or zinc alloy coated steel blank
WO2019155014A1